Hyperoside induces both autophagy and apoptosis in non-small cell lung cancer cells in vitro - FU Ting; WANG Ling; JIN Xiang-nan; SUI Hai-juan; LIU Zhou; JIN Ying (Acta Pharmacologica Sinica; Vol 37, No 4 (April 2016): Acta Pharmacologica Sinica, 2017)
Aim: Hyperoside (quercetin-3-O-β-D-galactopyranoside) is a flavonol glycoside found in plants of the genera Hypericum and Crataegus, which exhibits anticancer, anti-oxidant, and anti-inflammatory activities. In this study we investigated whether autophagy was involved in the anticancer mechanisms of hyperoside in human non-small cell lung cancer cells in vitro. Methods: Human non-small cell lung cancer cell line A549 was tested, and human bronchial epithelial cell line BEAS-2B was used for comparison. The expression of LC3-II, apoptotic and signaling proteins was measured using Western blotting. Autophagosomes were observed with MDC staining, LC3 immunocytochemistry, and GFP-LC3 fusion protein techniques. Cell viability was assessed using MTT assay. Results: Hyperoside (0.5, 1, 2 mmol/L) dose-dependently increased the expression of LC3-II and autophagosome numbers in A549 cells, but had no such effects in BEAS-2B cells. Moreover, hyperoside dose-dependently inhibited the phosphorylation of Akt, mTOR, p70S6K and 4E-BP1, but increased the phosphorylation of ERK1/2 in A549 cells. Insulin (200 nmol/L) markedly enhanced the phosphorylation of Akt and decreased LC3-II expression in A549 cells, which were reversed by pretreatment with hyperoside, whereas the MEK1/2 inhibitor U0126 (20 μmol/L) did not blocked hyperoside-induced LC3-II expression. Finally, hyperoside dose-dependently suppressed the cell viability and induced apoptosis in A549 cells, which were significantly attenuated by pretreatment with the autophagy inhibitor 3-methyladenine (2.5 mmol/L). Conclusion: Hyperoside induces both autophagy and apoptosis in human non-small cell lung cancer cells in vitro. The autophagy is induced through inhibiting the Akt/mTOR/p70S6K signal pathways, which contributes to anticancer actions of hyperoside.